Analisis Wacana Bahasa Gaul pada Media Sosial Twitter di Kalangan Remaja Periode Juni-Juli 2023 - Riana Afianti; Agus Wismanto; Azzah Nayla (Journal on Education, 2024)
This research aims to describe the slang on the @xxvnyyxx Twitter social media account among teenagers for the period June to July 2023, as well as to determine the influence of slang on the @xxvnyyxx Twitter social media account among teenagers for the period June to July 2023. This type of research is qualitative. . Data collection was carried out using documentation methods, listening techniques and note-taking techniques. Data analysis was carried out using the look and note technique. Presentation of the results of data analysis is carried out informally. The results of the research show that the use and influence of slang among teenagers is very large on the @xxvnyyx Twitter social media account among teenagers for the period June to July 2023 and there are influences resulting from the use of slang, namely positive influences and negative influences. Based on the results of the observation carried out on account@xxvnyyxx, a lot of slang is used.